Efeitos do anastrozol na periodontite induzida por ligadura em ratas ovariectomizadas - Melo, Iracema Matos de (2012)
Estrogen deficiency was shown to increase bone remodeling, may affect some bone diseases as periodontitis. Biosynthesis of this hormone is catalyzed by aromatase enzyme and her inhibition is important for breast cancer therapy. The patients who use aromatase inhibitors as Anastrozole (ANA) show greater number of fractures and lower bone density. Since estrogen role in the inflammatory response and the bone metabolism, besides those adverse effects of ANA and periodontitis is characterized by an inflammatory process that results in alveolar bone loss, the aim of this study was to investigate whether ANA affects the periodontitis in ovariectomized rats. For this, ANA (0.02, 0.1 and 0.5 mg/kg-v.o.) was evaluated in ligature-induced periodontits for 11 days in ovariectomized rats. Periodontitis was analyzed through macroscopy, histology and by myeloperoxidase (MPO) activity. Serum dosage of estrogen, leukogram, corporal mass variation and liver, renal and spleen functions were also analyzed. The ovariectomy reduced the serum levels of estrogen after 14 days, but did not worsen the periodontitis nor increased MPO activty when compared to sham ovariectomized (S-OVX) animals. Although, ANA did not increase alveolar bone loss (ABL), administration of this drug for 11 days increased the MPO activity. The ovariectomy combined or not with ANA no promoved any changes in liver, renal or spleen functions, but caused leukocytosis promoved by mononuclear cells at 11th day. Ovaricetomized animals that received saline (SAL) also showed more gain of corporal mass and ANA weight curve were similar to SAL curve. In conclusion, although the estrogen reduction for 25 days and the administration of anastrozole for 11 days did not increase the ABL, the ANA increased the MPO activity.